the The effect of biofertilization with Rhizobium bacteria and two types of PGPR bacteria on the formation of root nodules and the growth and production of Vicia Faba L.plants - حماد ياسر; محمد ابراهيم (Latakia University Journal -Biological Sciences Series, 2025)
Biofertilizers are products that contain microorganisms necessary for soil fertility and plant growth when added to the soil. They colonize the root zone when seeds or soil are inoculated with them, and stimulate plant growth by controlling the amount or availability of nutrients, by fixing atmospheric nitrogen, and dissolving Phosphorus, increasing organic matter in the soil and making it available to plants. The research aimed to study the effectiveness of inoculation with some types of plant growth-promoting rhizobacteria (PGPR) on Vicia Faba L. plant growth and root nodule formation: Growth indicators (plant height, fresh and dry weight of shoot and root shoots, number of effective and ineffective root nodules) were measured. And some soil chemical properties: pH, organic matter, total nitrogen, available phosphorus and potassium. The research was carried out in the 2023/2024 season in the nursery of the Faculty of Agricultural Engineering at Tishreen University. The results showed that inoculation with bacteria, singly or mixed, led to a significant increase in all treatments studied compared to the control not inoculated with bacteria. The best results were when inoculated with a mixture of the three types of RBF, with significant differences, as the plant height reached (83.21 cm/plant), and the weight The fresh and dry weight of the shoot (637.6 and 159.6 g/plant), respectively, and the fresh and dry weight of the root (31.8 and 22.4 g/plant), respectively. The number of effective root nodes reached (144.8) effective nodes, and the average production was (599.83 g/m2). ), while the percentage of organic matter was (3.62%), total nitrogen (0.198%), available phosphorus (41.11 mg/kg), and available potassium (717.6 mg/kg) compared to the healthy control not inoculated with bacteria.